The protector [videorecording (DVD)] - Jaa, Tony, 1976-; Phetthāi Wongkhamlao; Bongkod Kongmalai, 1985- (Dragon dynasty (Series), 2007)
Kham grew up with elephants in Thailand. To him elephants are majestic creatures, bred for peace, but prepared for war. When an evil Asian gang kidnap a bull and baby elephant during a festival, they are smuggled into Sydney, Australia. Kham must travel to a foreign land, and unravel a conspiracy that will reach into the highest levels of Australian law and business circles. With only his Muy Thai fighting techniques, and a disgraced Thai-descent police sergeant, he must reclaim his elephants, and his heritage.